A Systematic Review: Current Technology of Solid Carrier Formulation to Improve Viability and Effectiveness of Nitrogen-Fixing Inoculant - Ariani, Nabila Syifa; Simarmata, Tualar (Agrikultura, 2023)
Biofertilizers are a promising alternative solution to reduce the long-term adverse effects of chemical fertilizers and are increasingly important for promoting sustainable agriculture. Unfortunately, biofertilizers have a relatively short shelf life, and microbial effectiveness often decreases during storage and application. Therefore, innovation is needed regarding the formulation of biological fertilizer carriers that have the potential to maintain microbial viability and effectivity during storage. The comprehensive study was carried out using Systematic Literature Review (SLR) method by the search engine to evaluate and assess the current status of solid carrier formulation to improve the viability and effectiveness of biofertilizers inoculants. The results of a systematic review of scientific literature were obtained from as many as 149 articles from ScienceDirect and Scopus, and a total of 10 articles were chosen for further review. Several carrier materials have been reported can increase the viability and effectiveness of N-fixing inoculant. Each carrier material provides various benefits, such as increased microbial shelf life, microbial activity, and plant growth. Some carrier materials have the potential for further development in Indonesia.